2008
DOI: 10.1021/es7031407
|View full text |Cite
|
Sign up to set email alerts
|

Field Sampling Method for Quantifying Odorants in Humid Environments

Abstract: Most air quality studies in agricultural environments use thermal desorption analysis for quantifying semivolatile organic compounds (SVOCs) associated with odor. The objective of this study was to develop a robust sampling technique for measuring SVOCs in humid environments. Test atmospheres were generated at ambient temperatures (23 ± 1.5 °C) and 25, 50, and 80% relative humidity (RH). Sorbent material used included Tenax, graphitized carbon, and carbon molecular sieve (CMS). Sorbent tubes were challenged wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 36 publications
5
53
2
Order By: Relevance
“…Field sampling and analysis of sorbent tubes followed modified procedures developed in Trabue et al (2008a). In brief, air samples were collected on glass sorbent tubes (178 Â 6 mm diameter) containing a multi-bed sorbent packing of Carbopack C and Carbopack X (1:2 ratio v/v).…”
Section: Sorbent Tube Sampling and Analysis (To-17)mentioning
confidence: 99%
See 3 more Smart Citations
“…Field sampling and analysis of sorbent tubes followed modified procedures developed in Trabue et al (2008a). In brief, air samples were collected on glass sorbent tubes (178 Â 6 mm diameter) containing a multi-bed sorbent packing of Carbopack C and Carbopack X (1:2 ratio v/v).…”
Section: Sorbent Tube Sampling and Analysis (To-17)mentioning
confidence: 99%
“…Thermal desorption (TDS) parameters were exactly the same as Trabue et al (2008a). The PTV inlet method was modified using a glass bead/Carbopack C packed inlet (previously glass beads only) and using a 1 min delay in the purge split flow (previously 0.01 min delay) making this procedure essentially a splitless injection.…”
Section: Sorbent Tube Sampling and Analysis (To-17)mentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have identified and quantified the concentrations of gaseous compounds emitted from swine waste and swine operations (Lo et al, 2008;O'Neill and Phillips, 1992;Zahn et al, 1997;Schiffman et al, 2001;Zahn et al, 2001). Trabue et al (2008b) used sorbent tubes packed with Carbopack X and Carbopack C to collect air samples at approximately 1 m above the floor inside a tunnelventilated swine finishing building in Iowa. Using a gas chromatography-mass spectrometry (GC-MS) system to analyze the samples, they observed that butanoic acid (28.8 μg m ) were the compounds detected most often above their odor detection threshold values.…”
Section: ) the Emissions Of Specific Vocs Varied Between Seasons Simentioning
confidence: 99%